Informação, meio ambiente e atores sociais: mediação dos conflitos socioambientais - Aloisio Ruscheinsky (Ciências Sociais Unisinos)
In this article, different emphases to environmental issues are addressed from information in the pages of a newspaper and the resulting interpretations operated under environmental conflicts. The key point of the argument makes considerations of the circumstances of the production of information as a mediator or as a link between social actors in a context of social and environmental changes. The approach emphasizes the limitations and controversies that encompass the process of social information in a society marked by the movement of goods by a consumer culture, the environmental conflicts and the growing scarcity of natural resources. At the same time, this study emphasizes practices of social actors in civil society and public managers in terms of decision making for other social and environmental practices, as well as attempts of public policies enforcement.